Studi Pendahuluan Kualitas Air Untuk Pengembangan Budidaya Perikanan di Kecamatan Sampoinit Aceh Jaya Pasca Tsunami - Muchlisin Z.A, Muchlisin Z.A (Universitas Jambi, 2009)
The preliminary study of water quality assessment for developing aquaculture effortwas done in Sampoinit sub district for one week (1-8 December 2007). The objective of the presentstudy is to evaluate the suitability of sites for developing of aquaculture. The explorative surveymethod was used in this study by determine of several sampling points at identified sites. Thesurvey was covered four villages i.e. Meunasah Kulam, Crak Mong, Krueng No dan Pulo Raya. Theresults show that Meunasah Kulam, Crak Mong, Krueng No dan Pulo Raya were suitable forbrackish water aquaculture of Scylla serrata, Mugil sp, Tilapia mossambica), Tilapia nilotica andChannos channos, while Crak Mong was suitable for freshwater aquaculture of Clarias batrachusand Channa striata. A semi intensive of aquaculture was suitable to be developed.